2016
DOI: 10.1016/j.jelechem.2015.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol oxidation on shape-controlled platinum nanoparticles at different pHs: A combined in situ IR spectroscopy and online mass spectrometry study

Abstract: Ethanol oxidation on different shape-controlled platinum nanoparticles at different pHs was studied using electrochemical, Attenuated Total Reflection -Fourier Transform Infrared Spectroscopy (ATR-FTIR) and, especially, Differential Electrochemical Mass Spectrometry (DEMS) techniques, which gives interesting quantitative information about the products of ethanol oxidation. Two Pt nanoparticle samples were used for this purpose: (100) and (111) preferentially oriented Pt nanoparticles. The results are in agreem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…Regarding monometallic catalysts, Feliu and coworkers studied the ethanol oxidation in acid media on different shape‐controlled platinum nanoparticles: (100) and (111) predominantly oriented Pt nanoparticles with a preferential cubic and octahedron shape, respectively . FTIRS and DEMS studies demonstrated that the C−C bond breaking was more favored on cubic Pt NPs (2B in Scheme ), in agreement with the aforementioned results with Pt single crystals.…”
Section: Shape‐controlled Metal Nanoparticles For the Eormentioning
confidence: 55%
See 1 more Smart Citation
“…Regarding monometallic catalysts, Feliu and coworkers studied the ethanol oxidation in acid media on different shape‐controlled platinum nanoparticles: (100) and (111) predominantly oriented Pt nanoparticles with a preferential cubic and octahedron shape, respectively . FTIRS and DEMS studies demonstrated that the C−C bond breaking was more favored on cubic Pt NPs (2B in Scheme ), in agreement with the aforementioned results with Pt single crystals.…”
Section: Shape‐controlled Metal Nanoparticles For the Eormentioning
confidence: 55%
“…Whereas only the synthesis of monometallic high‐index facets NPs has been reported by using electrochemical methods, by the use of chemical methods have been reported also the synthesis of not only high‐index but also low‐index monometallic, bimetallic and trimetallic NPs, such as cubic, octahedral and rhombic dodecahedral NPs with predominantly {100}, {111} and {110} facets, respectively …”
Section: Shape‐controlled Metal Nanoparticles For the Eormentioning
confidence: 99%
“…Moreover, the direct correlation from the displayed result between the Pt(poly) and the Pt( hkl ) surfaces is not straightforward simple because once the most active surface domain starts oxidizing the organic molecule, the solution concentration changes for neighbor domains, which will activate at higher potentials. However, it can be used to understand its behavior and to prepare catalysts with predetermined surface orientation so that activity is maximized …”
Section: Resultsmentioning
confidence: 99%
“…3 (FTIR) [39][40][41][42][43], and High Performance Liquid Chromatography (HPLC) [16,44,45], which have helped to identify the reaction products. Acetaldehyde and acetic acid always emerge as the main products and reflect the stability of the C-C bond at lower DAFC operating temperatures 80-100 o C.…”
Section: Accepted Manuscriptmentioning
confidence: 99%